Trotskyists on Trial: Free Speech and Political Persecution since the Age of FDR - Palmer, Bryan D. (Labour / Le Travail, 2016)
The article reviews the book, "Trotskyists on Trial: Free Speech and Political Persecution since the Age of FDR," by Donna T. Haverty-Stacke.